A procedure to manage the production system in Cuban food companies - Campos Fernández, María de los Ángeles (2021)
The objective of this article is to design a procedure to manage the production system, considering the main technical-organizational and political-economic requirements of the process, as well as its key factors and essential elements. An exhaustive analysis of the consulted methodologies was carried out using selection variables. It was concluded that the proposed procedure improves production planning, organization and control in food companies.